Residencia universitaria en el Cercado de Lima espacios intermedios como elementos de cohesión social - Aliaga Montes, Hillary Marlen (2022)
There is currently a great demand for university residence in the city of Lima due to the lack of existing infrastructure on the part of the state and an inadequate offer in the real estate market for this group. The 85% of scholarships awarded annually in the National Scholarship Program (PRONABEC) are obtained by students from the provinces and rural regions who later seek to migrate to the capital to continue their higher studies in order to find better opportunities and new experiences. They are some of the most affected by the lack of this type of housing given their socioeconomic conditions. The present work of professional sufficiency is based on rethinking the design of a university residence so that it not only satisfies the need for accommodation of scholarship students, but also, to encourage interaction between them, considering that they come from different cultures and therefore different customs, perceptions and ways of living. To meet this objective, a study is made on the typology and its situation in Peru, on its most prominent international references and on theories that contemplate the actions of architecture in the creation of intercultural communities. Additionally, a contextual analysis is carried out to find out the best location in the city for a university residence according to the location of universities, higher education institutes, public transport routes and recreation areas. Consequently, a series of design guidelines are made for the composition of each environment that a student residence for scholarship holders in Lima must have. In the same way, strategies are established to locate this project in the urban environment that the district of Cercado de Lima presents, so it became a factor of urban change and improvement of the quality of the public spaces that exists near the chosen location. This urban regeneration aims for the students as well as for the neighbors. The use of the “inbetween” spaces stands out to generate a transition between the private and the public program and, above all, to create ideal settings for visual interactions, dialogues, cultural exchanges and unexpected encounters.